Impact of land development on water quantity and water quality in Peninsular Malaysia - Mohamad Suhaily Yusri Che Ngah; Zainudin Othman (Environmental Management Society, Malaysia, 2011)
The steady population growth in Malaysia has been responsible for the usage of relatively large volumes of water. Even though water quality has begun to attain some prominence, its relation to water quantity and to water system operation has been largely overlooked. Human activities frequently challenge the quantity and quality of water in Malaysian water resources. These include activities that use river water directly - such as irrigation and land-based activities that generate nutrients and pollutants, while also changing the runoff patterns of their catchments. A growing population with growing expectations places increasing pressure on our water resources, stretching their ability in maintaining the standards of water quantity and quality.